Federal Republic of Nigeria Diagnostic Review of Financial Consumer Protection : Key Findings and Recommendations - World Bank Group (World Bank, Washington, DC, 2018)
While only 44 percent of adults in Nigeria have an account at a formal financial institution, and only 2.5 percent have a mobile account, there are rapid innovations in both traditional and digital financial services that promote financial inclusion but also add complexity and risks for inexperienced consumers. Strengthening financial consumer protection (FCP) in Nigeria is therefore critical to ensure responsible and sustainable financial inclusion. This Diagnostic Review was conducted under the joint World Bank and IMF program to strengthen Nigeria's financial sector. The Central Bank of Nigeria (CBN) has already established a dedicated Consumer Protection Department and developed a high-level FCP Framework, however there are many areas for improvement. The Review analyzes the FCP regime in Nigeria's banking, non-bank financial institution (NBFI) and payment sectors, and offers tailored recommendations. Based on the 2017 World Bank Good Practices for Financial Consumer Protection, this assessment covers five topics in each of the abovementioned sectors: i) legal, regulatory, and supervisory framework; ii) disclosure and sales practices; iii) fair treatment and business conduct; iv) data privacy; and v) dispute resolution mechanisms. The Review summarizes the key findings and recommendations and then discusses them in detail.